Nutraceutical formulation based on a synergic combination of melatonin and palmitoylethanolamide for the management of allergic events - Maisto, Maria; Piccolo, Vincenzo; Marzocchi, Adua; Maresca, Daniela Claudia; Romano, Benedetta; Summa, Vincenzo; Tenore, Gian Carlo; Ercolano, Giuseppe; Ianaro, Angela (Frontiers in Nutrition, 2024)
The management of allergic events is a global growing health issue, especially in industrialized countries. This disease is an immune-mediated process, regulated by the interaction of immunoglobulin E (IgE) with an allergen, resulting in mast cell activation, which concerns the release of several immune-inflammatory modulators, i.e., histamine, -hexosaminidase, COX-2, IL-6, TNF- responsible for the main allergic-reaction associated symptoms. The aim of the present study was the efficacy evaluation of an alternative remedy, an innovative nutraceutical formulation (NF) based on the synergic combination of melatonin (MEL) and palmitoylethanolamide (PEA) for the prevention and treatment of immune disease. At first, the intestinal bioaccessibility of PEA and MEL in NF was assessed at 1.6 % and 36%, respectively. Then the MEL and PEA ability to modulate the release of immune-inflammatory modulators in the Human Mast Cell line (HMC-1.2) at their bioaccessible concentration was investigated. Our results underline that NF treatment was able to reduce COX-2 mRNA transcription levels (-30% vs STIM, p < 0.0001) in stimulated HMC-1.2 and to contract COX-2 enzymatic activity directly (IC50: 152 g /ml). Additionally, NF showed valuable ability in reducing histamine and -hexosaminidase release in stimulated HMC-1.2, as well as in decreasing TNF- and IL-6 mRNA transcription levels and protein production.